Effect of Q-switched pulses exposure on morphology, hydroxyapatite composition, and microhardness properties of human enamel - Apsari, Retna; Bidin, Noriah; Aminatun, -; Suhariningsih, -; Hartati, Sri; Yuliati, Anita; Yasin, Moh; Harun, Sulaiman Wadi (Laser Institute of America, 2011)
Ablation of healthy human enamel is demonstrated using a 8 ns pulses at wavelength of 1064 nm and 10Hz repetition rate from a Q -switched Nd:YAG laser. The ablation result shows that an enhanced structuring quality in comparison with non- Q -switched pulse exposure. The material removal remains localized in the area of the laser spot with no signs of collateral damage and cracks observed. As a comparison, exposure to longer pulses of 120 μs from non- Q -switched Nd:YAG laser increases the composition of hydroxyapatite as well as microhardness property of enamel, which produces a side effect of surface dehydration and crack. This study suggests that the application of Q -switched Nd:YAG laser as contactless drills in dentistry should be regarded as an alternative to the classical mechanical technique to improve the quality of the tooth treatment.